Location, location, location: The Dark Triad and Life History indicators in American, Singaporean, and Polish samples - JONASON, P. K. (Institutional Knowledge at Singapore Management University, 2012)
The current research examined the link between the Dark Triad traits and individual’s life histories in the USA (n = 264), Singapore (n = 185) and Poland (n = 177). It was hypothesized that relationships between the Dark Triad traits and fast life history indicators would be more pronounced in populations that experienced greater hardship and environmental unpredictability connected to socioeconomic stress and that this is because the Dark Triad traits represent a context-dependent, fast life histories strategy. Results showed that (1) in a society (i.e., Poland) that has suffered protracted periods of socioeconomic stress, there was a strong and more expansive link between the Dark Triad and life history indicators and (2) men scored higher than women did on the Dark Triad traits in all three locations. Results are discussed from a Life History Theory perspective.